Stenting for malignant colonic obstruction - Azar, Riad (2009)
Background: Self-expandable metal stent placement for palliation of malignant colonic obstruction for colorectal cancer (CRC) is safe and efficacious. In contrast, outcomes of stent placement for extracolonic malignancy (ECM) are unclear. Objective: To compare the success and complication rates of colorectal stenting in patients with CRC versus those with ECM. Design: Retrospective chart review. Setting: Tertiary-care academic medical center. Patients and Interventions: Between September 2000 and December 2007, all patients with malignant colon obstruction in whom endoscopy was performed with the intention of placing a colonic metal stent. Main Outcome Measurements: Technical and clinical success rates, surgical interventions, and procedure related complications. Results: Colonic stenting was performed for CRC in 34 patients and for ECM in 15 patients. Patients with CRC were more likely to have clinical success after all endoscopic therapy (94.1%) than those with ECM (20.0%) (P ! .0001). Surgical diversion to relieve persistent obstructive symptoms was required in significantly more patients with ECM. Five patients with ECM (33.3%) had at least one complication, including 2 deaths, compared with 3 patients with CRC (8.8%) (P Z .046). Only underlying ECM was predictive of failed colon stent placement by multivariate analysis (hazard ratio 21.0, P Z .0013). A history of radiation therapy was the sole predictor of complications (hazard ratio 7.8, P Z .048). Limitations: Single institution, retrospective analysis, relatively small sample size. Conclusions: Colon stenting for large-bowel obstruction from ECM is infrequently successful and is associated with a significantly higher risk of complications in comparison with patients with CRC.